(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Humankind has long been preoccupied with its youth. Inthe collective life of societies, each new generation of young people has beenrightly perceived as the rather fragile vessel by which the best of the past ofhard-won fruits of our painful and slippery steps up from the primordial mists– is transmitted into the present. Delinquency constitutes one of the majorsocial problems in both developed and developing societies. It refers tobehaviour under 18 years of age which is not acceptable to society and isgenerally regarded as calling for some kind of admonishment, punishment orcorrective action. Thus delinquent behaviour may range from truancy toincorrigibility and the use of illicit drugs to commitment of murder and otherserious crimes. It may be pointed out that the actual incidence of juveniledelinquency is difficult to determine, since many delinquent acts are neitherreported nor processed in the criminal justice system.